RELEVANSI SOSIOLOGI AGAMA DALAM KEHIDUPAN KEMASYARAKATAN - Mantik, Aliyah; Sodik, Jafar (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
Sociology of Islam is a scientific discipline that freezes its studies in the realm of Islamic community groups. Sociology of Islam seeks to portray Islamic community groups that have a social-cultural system that is built on their own system of values, beliefs, history, and morality. Sociology of religion tries to understand the meaning given by society to certain religious systems, by placing religion and human diversity as social phenomena. Sociology of religion includes efforts to develop and search for more appropriate concepts in accordance with the intent to better understand religious phenomena so that humans can understand religion as human interests and activities. Religion is related to needs, feelings, aspirations, and concerns some essential aspects of the human condition, so an understanding of the sociology of religion is concerned only with its effect on human historical experience and in the development of society. Basically, religion will give birth to society and grow to create a culture so that the dynamics of its development give birth to society and in the end can bring up religion again and this continues to rotate as well as causal relationships between one variable and another, this is because of the rotation of the three variables. interconnected and included as external factors, namely religion, culture, and society. The sociology of Islam reflects the religious attitude of Muslims in Indonesia which shows a three-phased historical and symbolic relationship pattern that can be summed up into four things, namely tensions in the formulation of the basic state, ideological tensions, state dictatorship, and majority domination.